Antioxidant high-strength glass fiber

By performing multi-layer coating and modification treatment on the glass fiber, glass fibers with piezoelectric conductive layer and antioxidant film are formed, which solves the problems of failure and poor noise reduction and damping performance in the prior art, and achieves efficient antioxidant and sound insulation damping effects.

CN119638218APending Publication Date: 2025-03-18周炳胜
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411543424.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-05-20
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing antioxidant treatment technology fails in high humidity and high temperature environments, and organic antioxidants have weak resistance to hydrolysis, poor compatibility of inorganic antioxidants, and poor noise reduction and damping performance of coatings.

Method used

By silver plating, deposition, copper plating and spraying the glass fiber, a piezoelectric conductive layer and an antioxidant film are formed. Combined with the modification treatment technology, chalone fibers are formed to enhance their antioxidant and sound-insulating damping properties.

Benefits of technology

It realizes the long-term antioxidant performance of glass fiber in high humidity and high temperature environments, and improves its sound insulation damping characteristics, meeting the high requirements for safety and environmental protection.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an antioxidant high-strength glass fiber, and relates to the technical field of glass fibers. According to the invention, the glass fiber is taken as a raw material, silver plating treatment, deposition treatment, copper plating treatment and spraying treatment are carried out in sequence to obtain a foam conductive network structure containing piezoelectric particles, sound can be converted into current, then the current is converted into heat energy, and the heat energy is dissipated, so that the glass fiber has sound insulation and damping properties; 2 '-hydroxy-4' (3-methyl-2-butenyloxy) acetophenone, 2, 3-dihydroxy-4-ethoxybenzaldehyde, phosphorus trichloride and decanoic acid are used for further modification, so that the surface has oxidation resistance, and hydrolysis is effectively resisted. The anti-oxidation high-strength glass fiber prepared by the invention has the effects of sound insulation, damping and long-acting oxidation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass fibers, in particular to an oxidation-resistant high-strength glass fiber. Background Art

[0002] Glass fiber has excellent properties such as good insulation, low thermal conductivity, and high strength, and is often used as a reinforcing material for coatings and cement. However, coatings are prone to oxidative degradation when they are in a high humidity and high temperature environment for a long time. The existing antioxidant treatment mainly involves adding organic or inorganic antioxidants, but organic antioxidants have weak hydrolysis resistance and lose their oxidation protection ability after a period of time, while inorganic antioxidants often face the problem of poor compatibility. Therefore, the present invention modifies glass fiber to make it have long-lasting antioxidant properties and good dispersibility, and is an excellent coating antioxidant.

[0003] In addition, the noise reduction and damping performance of the coating is poor, resulting in more mutual noise interference and affecting the quality of life. Existing sound insulation treatment technologies all use organic polymer materials as binders and are mixed with other sound insulation and damping materials. However, this type of coating will not only increase energy consumption, but also organic polymer materials are flammable and easy to release harmful substances, and their safety and environmental protection cannot meet people's increasingly stringent requirements. Moreover, most sound insulation and damping materials only have sound insulation functions and single performance. Summary of the invention

[0004] The object of the present invention is to provide an oxidation-resistant high-strength glass fiber and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: an antioxidant high-strength glass fiber, the preparation method of the antioxidant high-strength glass fiber comprises the following steps: using glass fiber as raw material, firstly subjecting it to silver plating treatment, deposition treatment, copper plating treatment, and spraying treatment in sequence to obtain piezoelectric conductive layer fiber, and then subjecting it to modification treatment to obtain an antioxidant layer.

[0006] Furthermore, the silver plating treatment is to immerse the glass fiber in 3-mercaptopropylmethyldimethoxysilane after pretreatment, react for a predetermined time, and then immerse it in ethylene glycol solution, and then add ferric chloride solution, silver nitrate solution and reducing solution, and react for a period of time to obtain silver-plated fiber; the deposition treatment is to place the silver-plated fiber in a mixed solution of ethanol and ammonia water, add tetraethyl orthosilicate and coupling agent KH570, and obtain silica fiber after reaction; the copper plating treatment is to pass hydrogen and copper acetylacetonate in an electric field-plasma environment, deposit for a period of time, calcine and wash to obtain foam copper fiber; the spraying treatment is to spray the piezoelectric powder precursor and gradient calcinate.

[0007] Furthermore, the modification treatment includes the following steps: mixing the piezoelectric conductive layer fiber, anhydrous ethanol, 2'-hydroxy-4' (3-methyl-2-butenyloxy) acetophenone and glacial acetic acid, reacting for a predetermined time to obtain a modified matrix; then mixing the modified matrix with anhydrous ethanol, sodium hydroxide solution and 2,3-dihydroxy-4-ethoxybenzaldehyde to react to obtain chalcone fiber; then mixing the chalcone fiber, toluene and triethylamine, reacting for a period of time, adding the decaned acid solution, continuing the reaction, filtering and drying.

[0008] Furthermore, a method for preparing an oxidation-resistant high-strength glass fiber comprises the following preparation steps: (1) Soak the pretreated glass fiber in an impregnation liquid of 4 to 10 times the mass of the pretreated glass fiber, heat it to 55 to 69°C, keep it warm for 3 to 6 hours, filter it, wash it with deionized water for 4 to 8 times, and dry it at 90 to 110°C and a vacuum degree of 20 to 40 kPa for 5 to 9 hours to obtain the modified glass fiber; (2) placing the modified glass fiber in an ethylene glycol solution of 25 to 35 times the mass of the modified glass fiber, wherein the mass ratio of polyvinyl pyrrolidone to ethylene glycol in the ethylene glycol solution is 1:30, adding a ferric chloride solution of 0.9 to 1.5 times the mass of the modified glass fiber, wherein the mass ratio of ferric chloride to ethylene glycol in the ferric chloride solution is 1:2287, reacting at 150 to 160°C and 100 to 200 rpm for 1 to 3 hours, adding a silver nitrate solution of 13 to 16 times the mass of the modified glass fiber at 1 to 3 mL / min, and then adding a reducing solution of 6 to 14 times the mass of the modified glass fiber at the same speed, reacting for 60 to 80 minutes, taking out, and washing with deionized water 5 to 9 times to obtain a silver-plated fiber; (3) The silver-plated fiber, anhydrous ethanol, 25% ammonia water, and deionized water were mixed in a mass ratio of 1:15:2:3-1:32:7:5, stirred at 50-100 rpm for 8-14 min, and then 2-5 times the mass of the silver-plated fiber of ethyl orthosilicate were added. After reacting at room temperature for 11-15 h, 0.1-0.3 times the mass of the silver-plated fiber of coupling agent KH570 and 4-8 times the mass of the silver-plated fiber of anhydrous ethanol were added, and the reaction was continued for 47-50 h. The fiber was washed with anhydrous ethanol and deionized water for 3-5 times in turn to obtain silica fiber. (4) Place the silica fiber in a plasma reactor under an external electric field of 25-40 V and evacuate to 5 × 10 -7 ~1×10 -6Pa, heated to 290-310°C in a nitrogen atmosphere, introduced hydrogen and copper acetylacetonate at a flow ratio of 1:1.7-1:2.5, deposited for 44-68 minutes, calcined at 400-480°C for 8-12 hours, immersed in 20% hydrofluoric acid with a mass fraction of 0.9-2.8 times the mass of the silica fiber, washed at 25-35kHz for 26-38 minutes, and dried at 40-50°C for 10-13 hours to obtain foamed copper fibers; (5) Spraying a piezoelectric powder precursor of 0.2 to 0.5 times the mass of the foamed copper fiber onto the foamed copper fiber, heating to 240 to 300 ° C, calcining for 4 to 8 hours, then heating to 500 to 560 ° C, calcining for 8 to 14 hours, and then heating to 750 to 810 ° C, calcining for 8 to 12 hours to obtain a piezoelectric conductive layer fiber; (6) Mix the piezoelectric conductive layer fiber, anhydrous ethanol, 2'-hydroxy-4'(3-methyl-2-butenyloxy)acetophenone and glacial acetic acid in a mass ratio of 1:28:0.3:0.1~1:34:0.6:0.1, react at 80~90°C for 8~11h under nitrogen protection, wash with anhydrous ethanol and distilled water for 3~5 times in sequence, and freeze-dry at -18~-6°C for 24~28h to obtain a modified matrix; (7) The modified matrix, anhydrous ethanol, a 10% sodium hydroxide solution and 2,3-dihydroxy-4-ethoxybenzaldehyde were mixed in a mass ratio of 1:1.7:4:0.7-1:3.3:7:0.9, stirred at 15-25°C and 100-200 rpm for 2.5-4.5 h, allowed to stand in an ice bath for 30-46 min, filtered, and washed with anhydrous ethanol for 4-6 times to obtain chalcone fiber; (8) Chalcone fiber, toluene and triethylamine were mixed in a mass ratio of 1:2:0.03 to 1:5:0.03. Under nitrogen protection, a phosphorus trichloride solution in an amount of 1.2 to 2.5 times the mass of the chalcone fiber was added at 60 to 70°C. The mixture was reacted for 30 to 42 minutes. The mixture was heated to 110 to 120°C. After reacting for 1.5 to 3 hours, a decaned acid solution in an amount of 3.5 to 5.4 times the mass of the chalcone fiber was added. The mixture was reacted for 3 to 6 hours. The mixture was filtered and dried at 40 to 50°C for 4 to 10 hours to obtain an antioxidant high-strength glass fiber.

[0009] Furthermore, the preparation method of the pretreated glass fiber in step (1) is as follows: after treating the glass fiber at 400-500° C. for 1-3 h, placing it in an acetone solution of 1-5 times the mass of the glass fiber, wherein the mass ratio of acetone to deionized water in the acetone solution is 3:7, washing it at 30-40 kHz for 20-30 min, filtering it, and then placing it in a roughening solution of 2-6 times the mass of the glass fiber, wherein the mass ratio of ammonium fluoride, 37% hydrochloric acid, and deionized water in the roughening solution is 1:0.7:60, oscillating it at the same frequency for 7-13 min, and filtering it.

[0010] Furthermore, the diameter of the glass fiber is 10-20 μm.

[0011] Furthermore, the silver nitrate solution in step (2) is a mixture of silver nitrate and ethylene glycol in a mass ratio of 1:55.7; the composition of the reducing solution is: 5 mL / L of nitric acid with a mass fraction of 68%, 7.5 g / L of glucose, 200 mL / L of ethanol, and the rest is deionized water.

[0012] Furthermore, in step (4), the discharge voltage of the plasma reactor is 18-22 kV, and the discharge frequency is 6-8 kHz.

[0013] Furthermore, the piezoelectric powder precursor in step (5) is a mixture of barium acetate, calcium acetate, titanium dioxide, zirconium dioxide, deionized water and citric acid in a mass ratio of 1:0.1:0.2:0.04:5:0.4 to 1:0.3:0.4:0.06:11:0.4.

[0014] Furthermore, the phosphorus trichloride solution in step (8) is a mixture of phosphorus trichloride and toluene in a mass ratio of 1:1.9 to 1:3.1; and the dodecanoic acid solution is a mixture of dodecanoic acid, toluene, and triethylamine in a mass ratio of 1:1.9:0.2 to 1:2.6:0.2.

[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: The invention uses glass fiber as raw material and sequentially coats a piezoelectric conductive layer and an anti-oxidation film to achieve anti-oxidation and sound insulation and damping properties.

[0016] Firstly, the invention performs silver plating treatment, uses 3-mercaptopropylmethyldimethoxysilane for modification treatment, introduces mercapto groups on the surface of glass fibers, adsorbs silver ions through coordination reaction, and gradually grows to form silver nanowires under the action of polyols and nucleating agents, and overlaps with each other to form a network; then performs deposition treatment, deposits and coats silicon dioxide microspheres on the surface of the silver nanowires under the cross-linking action of a coupling agent; then performs copper plating treatment, atomizes acetylacetonate copper, uses the reduction performance of hydrogen plasma to form gaseous copper atoms, and after introducing an external electric field, generates charges on the surface of silicon dioxide, and at the same time, the gaseous copper atoms are impacted by space electrons to give charges, It obtains more energy and is effectively adsorbed on the surface of silica to form a copper coating. After calcination, the copper coatings are bonded to each other. Due to the ductility of silver, it reacts with the glass fiber and copper at the interface to promote interface bonding, thereby forming connecting belts. The silica is then removed with acid to form foamed copper, which is entangled with the silver nanowires to form a conductive network. Then, it is sprayed to adsorb the piezoelectric powder precursor in the foamed copper. While calcining to form piezoelectric powder, it adheres to the inner wall of the foamed copper at high temperature. Under sound or vibration, the piezoelectric powder generates voltage, converts the absorbed noise into current and dissipates it along the conductive network as heat energy, so that the glass fiber has sound insulation and damping properties.

[0017] Secondly, the hydroxyl group of 2'-hydroxy-4'(3-methyl-2-butenyloxy)acetophenone is condensed with the hydroxyl group on the surface of the piezoelectric conductive layer and grafted on the surface; the acetophenone group is then used to condense 2,3-dihydroxy-4-ethoxybenzaldehyde to obtain a chalcone compound, which can effectively remove free radicals generated by the degradation of the polymer coating under light and high temperature, so that the glass fiber has an antioxidant effect; the two hydroxyl groups of 2,3-dihydroxy-4-ethoxybenzaldehyde react with phosphorus trichloride to form a chlorinated dioxaphosphorus heterocyclic compound, and then the decanic acid is reacted with chloride ions to obtain a phosphite group, forming a hindered phenol bisphenol radical that can terminate the peroxyl radical, and the chalcone group works together to improve the antioxidant property of the glass fiber, and the long-chain alkyl group is used to block the end to prevent the hydrolysis of the antioxidant activity on the surface of the glass fiber, thereby enhancing its antioxidant effect. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0019] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the oxidation-resistant high-strength glass fibers prepared in the following examples are as follows: Anti-oxidation high-strength glass fiber, polymer emulsion, thickener, pure water and defoaming agent were mixed in a mass ratio of 1:3:0.005:0.7:0.06, applied to steel plates to the same thickness, and the antioxidant and sound insulation and damping effects were tested.

[0020] Antioxidation: Yellowing resistance test was carried out according to GB / T23987, and the product was placed at 60℃ and 75% humidity for 96 hours, and then yellowing resistance test was carried out again.

[0021] Sound insulation and damping: refer to HG / T5058 for sound insulation and damping effect test.

[0022] Example 1 A method for preparing an oxidation-resistant high-strength glass fiber, the method for preparing an oxidation-resistant high-strength glass fiber mainly comprises the following preparation steps: (1) After treating a glass fiber with a diameter of 10 μm at 400°C for 3 hours, the glass fiber is placed in an acetone solution with a mass ratio of 1 times the mass of the glass fiber, wherein the mass ratio of acetone to deionized water in the acetone solution is 3:7, washed at 30 kHz for 30 minutes, filtered, and then placed in a roughening solution with a mass ratio of 2 times the mass of the glass fiber, wherein the mass ratio of ammonium fluoride, 37% hydrochloric acid, and deionized water in the roughening solution is 1:0.7:60, oscillated at the same frequency for 13 minutes, and filtered to obtain a pretreated glass fiber; the pretreated glass fiber is immersed in an impregnation solution with a mass ratio of 4 times the mass of the pretreated glass fiber, heated to 55°C, kept warm for 6 hours, filtered, washed with deionized water 4 times, and dried at 90°C and a vacuum degree of 20 kPa for 5 hours to obtain a modified glass fiber; (2) placing the modified glass fiber in an ethylene glycol solution of 25 times the mass of the modified glass fiber, wherein the mass ratio of polyvinyl pyrrolidone to ethylene glycol in the ethylene glycol solution is 1:30, adding a ferric chloride solution of 0.9 times the mass of the modified glass fiber, wherein the mass ratio of ferric chloride to ethylene glycol in the ferric chloride solution is 1:2287, reacting at 150°C and 100 rpm for 3 hours, adding a silver nitrate solution of 13 times the mass of the modified glass fiber at 1 mL / min, wherein the mass ratio of silver nitrate to ethylene glycol in the silver nitrate solution is 1:55.7, and then adding a reducing solution of 6 times the mass of the modified glass fiber at the same speed, reacting for 60 minutes, taking out, and washing with deionized water 5 times to obtain a silver-plated fiber; the composition of the reducing solution is: 5 mL / L of nitric acid with a mass fraction of 68%, 7.5 g / L of glucose, 200 mL / L of ethanol, and the rest is deionized water; (3) Silver-plated fiber, anhydrous ethanol, 25% ammonia water, and deionized water were mixed in a mass ratio of 1:15:2:3, stirred at 50 rpm for 14 min, and then ethyl orthosilicate (2 times the mass of the silver-plated fiber) was added. After reacting at room temperature for 11 h, coupling agent KH570 (0.1 times the mass of the silver-plated fiber) and anhydrous ethanol (4 times the mass of the silver-plated fiber) were added. The reaction was continued for 47 h, and the fiber was washed with anhydrous ethanol and deionized water three times in sequence to obtain silica fiber. (4) Under an external electric field of 25 V, the silica fiber was placed in a plasma reactor with a discharge voltage of 18 kV and a discharge frequency of 6 kHz and evacuated to 5 × 10 -7 Pa, heated to 290 ° C in a nitrogen atmosphere, introduced hydrogen and copper acetylacetonate at a flow ratio of 1:1.7, deposited for 68 minutes, calcined at 400 ° C for 12 hours, immersed in 20% hydrofluoric acid with a mass fraction of 0.9 times the mass of the silica fiber, washed at 25 kHz for 38 minutes, and dried at 40 ° C for 13 hours to obtain foamed copper fibers; (5) Mix barium acetate, calcium acetate, titanium dioxide, zirconium dioxide, deionized water and citric acid in a mass ratio of 1:0.1:0.2:0.04:5:0.4 to obtain a piezoelectric powder precursor; spray the piezoelectric powder precursor 0.2 times the mass of the foam copper fiber onto the foam copper fiber, heat to 240°C, calcine for 8 hours, then heat to 500°C, calcine for 14 hours, continue to heat to 750°C, calcine for 12 hours, and obtain a piezoelectric conductive layer fiber; (6) The piezoelectric conductive layer fiber, anhydrous ethanol, 2'-hydroxy-4'(3-methyl-2-butenyloxy)acetophenone and glacial acetic acid were mixed in a mass ratio of 1:28:0.3:0.1, reacted at 80°C for 11 hours under nitrogen protection, washed with anhydrous ethanol and distilled water three times in sequence, and freeze-dried at -18°C for 24 hours to obtain a modified matrix; (7) The modified matrix, anhydrous ethanol, a 10% sodium hydroxide solution and 2,3-dihydroxy-4-ethoxybenzaldehyde were mixed in a mass ratio of 1:1.7:4:0.7, stirred at 15°C and 100 rpm for 4.5 h, allowed to stand in an ice bath for 30 min, filtered, and washed with anhydrous ethanol four times to obtain chalcone fibers; (8) Chalcone fiber, toluene and triethylamine were mixed in a mass ratio of 1:2:0.03. Under nitrogen protection, a phosphorus trichloride solution in an amount 1.2 times the mass of the chalcone fiber was added at 60°C. The mass ratio of phosphorus trichloride to toluene in the phosphorus trichloride solution was 1:1.9. After reacting for 42 minutes, the mixture was heated to 110°C. After reacting for 3 hours, a decaned acid solution in an amount 3.5 times the mass of the chalcone fiber was added. The mass ratio of decaned acid, toluene and triethylamine in the decaned acid solution was 1:1.9:0.2. The mixture was reacted for 3 hours, filtered and dried at 40°C for 10 hours to obtain an antioxidant high-strength glass fiber.

[0023] Example 2 A method for preparing an oxidation-resistant high-strength glass fiber, the method for preparing an oxidation-resistant high-strength glass fiber mainly comprises the following preparation steps: (1) After treating a glass fiber with a diameter of 15 μm at 450°C for 2 h, the glass fiber was placed in an acetone solution 3 times the mass of the glass fiber, in which the mass ratio of acetone to deionized water was 3:7, washed at 35 kHz for 25 min, filtered, and then placed in a roughening solution 4 times the mass of the glass fiber, in which the mass ratio of ammonium fluoride, 37% hydrochloric acid, and deionized water was 1:0.7:60, oscillated at the same frequency for 10 min, and filtered to obtain a pretreated glass fiber; the pretreated glass fiber was immersed in an impregnation solution 7 times the mass of the pretreated glass fiber, heated to 62°C, kept warm for 4.5 h, filtered, washed with deionized water 6 times, and dried at 100°C and a vacuum degree of 30 kPa for 7 h to obtain a modified glass fiber; (2) placing the modified glass fiber in an ethylene glycol solution 30 times the mass of the modified glass fiber, wherein the mass ratio of polyvinyl pyrrolidone to ethylene glycol in the ethylene glycol solution is 1:30, adding a ferric chloride solution 1.2 times the mass of the modified glass fiber, wherein the mass ratio of ferric chloride to ethylene glycol in the ferric chloride solution is 1:2287, reacting at 155°C and 150rpm for 2h, adding a silver nitrate solution 14.5 times the mass of the modified glass fiber at 2mL / min, wherein the mass ratio of silver nitrate to ethylene glycol in the silver nitrate solution is 1:55.7, and then adding a reducing solution 10 times the mass of the modified glass fiber at the same speed, reacting for 70min, taking out, and washing with deionized water 7 times to obtain a silver-plated fiber; the composition of the reducing solution is: 5mL / L nitric acid with a mass fraction of 68%, 7.5g / L glucose, 200mL / L ethanol, and the rest is deionized water; (3) Silver-plated fiber, anhydrous ethanol, 25% ammonia water, and deionized water were mixed in a mass ratio of 1:23.5:4.5:4, stirred at 70 rpm for 11 min, and then 3.5 times the mass of the silver-plated fiber of tetraethyl orthosilicate was added. After reacting at room temperature for 13 h, 0.2 times the mass of the silver-plated fiber of coupling agent KH570 and 6 times the mass of the silver-plated fiber of anhydrous ethanol were added. The reaction was continued for 48.5 h, and the fiber was washed with anhydrous ethanol and deionized water four times in sequence to obtain silica fiber. (4) Under an applied electric field of 32 V, the silica fiber was placed in a plasma reactor with a discharge voltage of 20 kV and a discharge frequency of 7 kHz and evacuated to 7.5 × 10 -7 Pa, heated to 300 ° C in a nitrogen atmosphere, introduced hydrogen and copper acetylacetonate at a flow ratio of 1:2.1, deposited for 56 min, calcined at 440 ° C for 10 h, immersed in 20% hydrofluoric acid with a mass fraction of 1.8 times the mass of the silica fiber, washed at 30 kHz for 32 min, and dried at 45 ° C for 11.5 h to obtain foamed copper fiber; (5) Mix barium acetate, calcium acetate, titanium dioxide, zirconium dioxide, deionized water and citric acid in a mass ratio of 1:0.2:0.3:0.05:8:0.4 to obtain a piezoelectric powder precursor; spray the piezoelectric powder precursor 0.35 times the mass of the foam copper fiber onto the foam copper fiber, heat to 270°C, calcine for 6 hours, then heat to 530°C, calcine for 11 hours, continue to heat to 780°C, calcine for 10 hours, and obtain a piezoelectric conductive layer fiber; (6) The piezoelectric conductive layer fiber, anhydrous ethanol, 2'-hydroxy-4'(3-methyl-2-butenyloxy)acetophenone and glacial acetic acid were mixed in a mass ratio of 1:31:0.45:0.1, reacted at 85°C for 9.5 hours under nitrogen protection, washed with anhydrous ethanol and distilled water for 4 times, and freeze-dried at -12°C for 26 hours to obtain a modified matrix; (7) The modified substrate, anhydrous ethanol, 10% sodium hydroxide solution and 2,3-dihydroxy-4-ethoxybenzaldehyde were mixed in a mass ratio of 1:2.5:5.5:0.8, stirred at 20 °C and 150 rpm for 3.5 h, allowed to stand in an ice bath for 38 min, filtered, and washed with anhydrous ethanol five times to obtain chalcone fibers; (8) Chalcone fiber, toluene and triethylamine were mixed in a mass ratio of 1:3.5:0.03. Under nitrogen protection, a phosphorus trichloride solution in an amount 1.9 times the mass of the chalcone fiber was added at 65°C. The mass ratio of phosphorus trichloride to toluene in the phosphorus trichloride solution was 1:2.5. After reacting for 36 minutes, the mixture was heated to 115°C. After reacting for 2.3 hours, a decaned acid solution in an amount 4.5 times the mass of the chalcone fiber was added. The mass ratio of decaned acid, toluene and triethylamine in the decaned acid solution was 1:2.2:0.2. The mixture was reacted for 4.5 hours. The mixture was filtered and dried at 45°C for 7 hours to obtain an antioxidant high-strength glass fiber.

[0024] Example 3 A method for preparing an oxidation-resistant high-strength glass fiber, the method for preparing an oxidation-resistant high-strength glass fiber mainly comprises the following preparation steps: (1) After treating a glass fiber with a diameter of 20 μm at 500°C for 1 hour, the glass fiber is placed in an acetone solution 5 times the mass of the glass fiber, the mass ratio of acetone to deionized water in the acetone solution is 3:7, washed at 40kHz for 20 minutes, filtered, and then placed in a roughening solution 6 times the mass of the glass fiber, the mass ratio of ammonium fluoride, 37% hydrochloric acid, and deionized water in the roughening solution is 1:0.7:60, oscillated at the same frequency for 7 minutes, and filtered to obtain a pretreated glass fiber; the pretreated glass fiber is immersed in an impregnation solution 10 times the mass of the pretreated glass fiber, heated to 69°C, kept warm for 3 hours, filtered, washed with deionized water 8 times, and dried at 110°C and a vacuum degree of 40 kPa for 9 hours to obtain a modified glass fiber; (2) placing the modified glass fiber in an ethylene glycol solution 35 times the mass of the modified glass fiber, wherein the mass ratio of polyvinyl pyrrolidone to ethylene glycol in the ethylene glycol solution is 1:30, adding a ferric chloride solution 1.5 times the mass of the modified glass fiber, wherein the mass ratio of ferric chloride to ethylene glycol in the ferric chloride solution is 1:2287, reacting at 160°C and 200rpm for 1h, adding a silver nitrate solution 16 times the mass of the modified glass fiber at 3mL / min, wherein the mass ratio of silver nitrate to ethylene glycol in the silver nitrate solution is 1:55.7, and then adding a reducing solution 14 times the mass of the modified glass fiber at the same speed, reacting for 80min, taking out, and washing with deionized water 9 times to obtain a silver-plated fiber; the composition of the reducing solution is: 5mL / L nitric acid with a mass fraction of 68%, 7.5g / L glucose, 200mL / L ethanol, and the rest is deionized water; (3) Silver-plated fiber, anhydrous ethanol, 25% ammonia water, and deionized water were mixed in a mass ratio of 1:32:7:5, stirred at 100 rpm for 8 min, and then 5 times the mass of the silver-plated fiber was added with tetraethyl orthosilicate. After reacting at room temperature for 15 h, 0.3 times the mass of the silver-plated fiber coupling agent KH570 and 8 times the mass of the silver-plated fiber were added with anhydrous ethanol. The reaction was continued for 50 h, and the fiber was washed with anhydrous ethanol and deionized water for 5 times in sequence to obtain silica fiber. (4) Under an external electric field of 40 V, the silica fiber was placed in a plasma reactor with a discharge voltage of 22 kV and a discharge frequency of 8 kHz and evacuated to a pressure of 1 × 10 -6 Pa, heated to 310 ° C in a nitrogen atmosphere, introduced hydrogen and copper acetylacetonate at a flow ratio of 1:2.5, deposited for 44 minutes, calcined at 480 ° C for 8 hours, immersed in 20% hydrofluoric acid with a mass fraction of 8 times the mass of silica fiber, washed at 35 kHz for 26 minutes, and dried at 50 ° C for 10 hours to obtain foam copper fiber; (5) Mix barium acetate, calcium acetate, titanium dioxide, zirconium dioxide, deionized water and citric acid in a mass ratio of 1:0.3:0.4:0.06:11:0.4 to obtain a piezoelectric powder precursor; spray the piezoelectric powder precursor 0.5 times the mass of the foam copper fiber onto the foam copper fiber, heat to 300°C, calcine for 4 hours, then heat to 560°C, calcine for 8 hours, continue to heat to 810°C, calcine for 8 hours, and obtain a piezoelectric conductive layer fiber; (6) The piezoelectric conductive layer fiber, anhydrous ethanol, 2'-hydroxy-4'(3-methyl-2-butenyloxy)acetophenone and glacial acetic acid were mixed in a mass ratio of 1:34:0.6:0.1, reacted at 90°C for 8 hours under nitrogen protection, washed with anhydrous ethanol and distilled water for 5 times in sequence, and freeze-dried at -6°C for 28 hours to obtain a modified matrix; (7) The modified matrix, anhydrous ethanol, a 10% sodium hydroxide solution and 2,3-dihydroxy-4-ethoxybenzaldehyde were mixed in a mass ratio of 1:3.3:7:0.9, stirred at 25°C and 200 rpm for 2.5 h, allowed to stand in an ice bath for 46 min, filtered, and washed with anhydrous ethanol for 6 times to obtain chalcone fibers; (8) Chalcone fiber, toluene and triethylamine were mixed in a mass ratio of 1:5:0.03. Under nitrogen protection, a phosphorus trichloride solution of 2.5 times the mass of the chalcone fiber was added at 70°C. The mass ratio of phosphorus trichloride to toluene in the phosphorus trichloride solution was 1:3.1. After reacting for 30 minutes, the mixture was heated to 120°C. After reacting for 1.5 hours, a decaned acid solution of 5.4 times the mass of the chalcone fiber was added. The mass ratio of decaned acid, toluene and triethylamine in the decaned acid solution was 1:2.6:0.2. The mixture was reacted for 6 hours, filtered and dried at 50°C for 4 hours to obtain an antioxidant high-strength glass fiber.

[0025] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that there are no steps (1) and (2), and step (3) is changed to: glass fiber, anhydrous ethanol, 25% ammonia water, and deionized water are mixed in a mass ratio of 1:23.5:4.5:4, stirred at 70 rpm for 11 minutes, and then 3.5 times the mass of glass fiber ethyl orthosilicate is added. After reacting at room temperature for 13 hours, 0.2 times the mass of glass fiber coupling agent KH570 and 6 times the mass of glass fiber anhydrous ethanol are added, and the reaction is continued for 48.5 hours. The fiber is washed with anhydrous ethanol and deionized water four times in sequence to obtain silica fiber. The remaining preparation steps are the same as those in Example 2.

[0026] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that step (3) is omitted and step (4) is changed to: placing the silver-plated fiber in a plasma reactor with a discharge voltage of 20 kV and a discharge frequency of 7 kHz under an applied electric field of 32 V, and evacuating the vacuum to 7.5×10 - 7 Pa, heated to 300°C in a nitrogen atmosphere, introduced hydrogen and copper acetylacetonate at a flow ratio of 1:2.1, deposited for 56 minutes, calcined at 440°C for 10 hours, immersed in 20% hydrofluoric acid with a mass fraction of 1.8 times the mass of the silver-plated fiber, washed at 30kHz for 32 minutes, and dried at 45°C for 11.5 hours to obtain foamed copper fiber. The remaining preparation steps are the same as in Example 2.

[0027] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that step (4) is different. Step (4) is changed to: placing the silica fiber in a plasma reactor with a discharge voltage of 20 kV and a discharge frequency of 7 kHz, and evacuating the vacuum to 7.5×10 -7Pa, heated to 300°C in a nitrogen atmosphere, introduced hydrogen and copper acetylacetonate at a flow ratio of 1:2.1, deposited for 56 minutes, calcined at 440°C for 10 hours, immersed in 20% hydrofluoric acid with a mass fraction of 1.8 times the mass of the silica fiber, washed at 30kHz for 32 minutes, and dried at 45°C for 11.5 hours to obtain foamed copper fiber. The remaining preparation steps are the same as in Example 2.

[0028] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that step (4) is different. Step (4) is changed to: under an external electric field of 32V, the silica fiber is placed in a container and evacuated to 7.5×10 -7 Pa, heated to 300°C in a nitrogen atmosphere, introduced hydrogen and copper acetylacetonate at a flow ratio of 1:2.1, deposited for 56 minutes, calcined at 440°C for 10 hours, immersed in 20% hydrofluoric acid with a mass fraction of 1.8 times the mass of the silica fiber, washed at 30kHz for 32 minutes, and dried at 45°C for 11.5 hours to obtain foamed copper fiber. The remaining preparation steps are the same as in Example 2.

[0029] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that there is no step (5), and step (6) is changed to: the foam copper fiber, anhydrous ethanol, 2'-hydroxy-4'(3-methyl-2-butenyloxy)acetophenone and glacial acetic acid are mixed in a mass ratio of 1:31:0.45:0.1, reacted at 85°C for 9.5 under nitrogen protection, washed with anhydrous ethanol and distilled water for 4 times, and freeze-dried at -12°C for 26 hours to obtain a modified matrix. The remaining preparation steps are the same as those in Example 2.

[0030] Comparative Example 6 The difference between Comparative Example 6 and Example 2 is that there is no step (7), and step (8) is changed to: the modified substrate, toluene and triethylamine are mixed in a mass ratio of 1:3.5:0.03, and under nitrogen protection, a phosphorus trichloride solution of 1.9 times the mass of the modified substrate is added at 65° C., the mass ratio of phosphorus trichloride to toluene in the phosphorus trichloride solution is 1:2.5, after reacting for 36 minutes, heated to 115° C., reacted for 2.3 hours, and then a dodecanoic acid solution of 4.5 times the mass of the modified substrate is added, the mass ratio of dodecanoic acid, toluene and triethylamine in the dodecanoic acid solution is 1:2.2:0.2, reacted for 4.5 hours, filtered, and dried at 45° C. for 7 hours to obtain an antioxidant high-strength glass fiber. The remaining preparation steps are the same as those in Example 2.

[0031] Comparative Example 7 The difference between Comparative Example 7 and Example 2 is that step (8) is different. Step (8) is changed to: placing the chalcone fiber in a decaned acid solution with a mass ratio of 4.5 times that of the chalcone fiber, wherein the mass ratio of decaned acid, toluene and triethylamine in the decaned acid solution is 1:2.2:0.2, reacting for 4.5 hours, filtering, and drying at 45° C. for 7 hours to obtain an antioxidant high-strength glass fiber. The remaining preparation steps are the same as those in Example 2.

[0032] Comparative Example 8 The difference between Comparative Example 8 and Example 2 lies in the difference in step (8), where step (8) is changed to: chalcone fiber, toluene and triethylamine are mixed in a mass ratio of 1:3.5:0.03, and a phosphorus trichloride solution of 1.9 times the mass of the chalcone fiber is added at 65° C. under nitrogen protection, wherein the mass ratio of phosphorus trichloride to toluene in the phosphorus trichloride solution is 1:2.5, and after reacting for 36 minutes, the mixture is heated to 115° C. and reacted for 2.3 hours to obtain an antioxidant high-strength glass fiber. The remaining preparation steps are the same as those in Example 2.

[0033] Effect example Table 1 below shows the performance analysis results of coatings prepared using the oxidation-resistant high-strength glass fibers of Examples 1 to 3 of the present invention and Comparative Examples 1 to 8.

[0034] Table 1 Yellowing resistance (∆E) Yellowing resistance after hydrolysis (∆E) Weighted sound insulation increase (dB) <![CDATA[-10°C complex loss factor (η c )]]> <![CDATA[Complex loss factor at 20 °C (η c )]]> <![CDATA[Complex loss factor (η at 50°C c )]]> Example 1 0.6 0.9 5 0.08 0.14 0.11 Example 2 0.3 0.4 6 0.10 0.15 0.12 Example 3 0.4 0.7 5 0.09 0.12 0.10 Comparative Example 1 1.0 1.5 3 0.03 0.08 0.02 Comparative Example 2 0.8 1.2 2 0.02 0.06 0.03 Comparative Example 3 0.6 1.0 3 0.02 0.05 0.04 Comparative Example 4 0.7 1.0 1 0.01 0.03 0.01 Comparative Example 5 18.3 39.0 4 0.05 0.11 0.06 Comparative Example 6 18.0 32.7 4 0.05 0.12 0.05 Comparative Example 7 13.1 26.6 5 0.06 0.11 0.05 Comparative Example 8 1.1 19.8 4 0.07 0.13 0.07 From the comparison of the experimental data of yellowing resistance before and after hydrolysis between the embodiment and the comparative example, it can be found that the product utilizes 2'-hydroxy-4'(3-methyl-2-butenyloxy)acetophenone, 2,3-dihydroxy-4-ethoxybenzaldehyde, phosphorus trichloride and decanoic acid to react to form terminal long-chain compounds, which prevent the hydrolysis of the antioxidant activity on the surface of the glass fiber and enhance its antioxidant effect, and at the same time form a chalcone group-phosphite group, which work together to improve the antioxidant property of the glass fiber; from the comparison of the experimental data of the weighted sound insulation increase and the loss factor at various temperatures between the embodiment and the comparative example, it can be found that after the glass fiber is subjected to silver plating, deposition, copper plating, spraying and other treatments, a foam conductive network containing piezoelectric ceramics is formed on the surface of the product, and under sound or vibration, the piezoelectric powder generates voltage, converts the absorbed noise into current and dissipates it as heat along the conductive network, so that the glass fiber has sound insulation and damping properties.

[0035] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An oxidation-resistant high-strength glass fiber, characterized in that: The method for preparing the anti-oxidation high-strength glass fiber comprises the following steps: using glass fiber as a raw material, firstly performing silver plating treatment, deposition treatment, copper plating treatment, and spraying treatment in sequence to obtain a piezoelectric conductive layer fiber, and then performing a modification treatment to obtain an anti-oxidation layer; The silver plating treatment is to soak the glass fiber in 3-mercaptopropylmethyldimethoxysilane after pretreatment, react for a predetermined time, soak it in ethylene glycol solution, then add ferric chloride solution, silver nitrate solution and reducing solution, react for a period of time to obtain silver-plated fiber; the deposition treatment is to place the silver-plated fiber in a mixed solution of ethanol and ammonia water, add tetraethyl orthosilicate and coupling agent KH570, and react to obtain silica fiber; the copper plating treatment is to introduce hydrogen and copper acetylacetonate in an electric field-plasma environment, deposit for a period of time, calcine and wash, and obtain foam copper fiber; the spraying treatment is to spray the piezoelectric powder precursor and gradient calcinate; The method for preparing the antioxidant high-strength glass fiber mainly comprises the following preparation steps: (1) After treating a glass fiber with a diameter of 15 μm at 450°C for 2 h, the glass fiber was placed in an acetone solution 3 times the mass of the glass fiber, in which the mass ratio of acetone to deionized water was 3:7, washed at 35 kHz for 25 min, filtered, and then placed in a roughening solution 4 times the mass of the glass fiber, in which the mass ratio of ammonium fluoride, 37% hydrochloric acid, and deionized water was 1:0.7:60, oscillated at the same frequency for 10 min, and filtered to obtain a pretreated glass fiber; the pretreated glass fiber was immersed in an impregnation solution 7 times the mass of the pretreated glass fiber, heated to 62°C, kept warm for 4.5 h, filtered, washed with deionized water 6 times, and dried at 100°C and a vacuum degree of 30 kPa for 7 h to obtain a modified glass fiber; (2) placing the modified glass fiber in an ethylene glycol solution 30 times the mass of the modified glass fiber, wherein the mass ratio of polyvinyl pyrrolidone to ethylene glycol in the ethylene glycol solution is 1:30, adding a ferric chloride solution 1.2 times the mass of the modified glass fiber, wherein the mass ratio of ferric chloride to ethylene glycol in the ferric chloride solution is 1:2287, reacting at 155°C and 150rpm for 2h, adding a silver nitrate solution 14.5 times the mass of the modified glass fiber at 2mL / min, wherein the mass ratio of silver nitrate to ethylene glycol in the silver nitrate solution is 1:55.7, and then adding a reducing solution 10 times the mass of the modified glass fiber at the same speed, reacting for 70min, taking out, and washing with deionized water 7 times to obtain a silver-plated fiber; the composition of the reducing solution is: 5mL / L nitric acid with a mass fraction of 68%, 7.5g / L glucose, 200mL / L ethanol, and the rest is deionized water; (3) Silver-plated fiber, anhydrous ethanol, 25% ammonia water, and deionized water were mixed in a mass ratio of 1:23.5:4.5:4, stirred at 70 rpm for 11 min, and then 3.5 times the mass of the silver-plated fiber of tetraethyl orthosilicate was added. After reacting at room temperature for 13 h, 0.2 times the mass of the silver-plated fiber of coupling agent KH570 and 6 times the mass of the silver-plated fiber of anhydrous ethanol were added. The reaction was continued for 48.5 h, and the fiber was washed with anhydrous ethanol and deionized water four times in sequence to obtain silica fiber. (4) Under an applied electric field of 32 V, the silica fiber was placed in a plasma reactor with a discharge voltage of 20 kV and a discharge frequency of 7 kHz and evacuated to 7.5 × 10 -7 Pa, heated to 300 ° C in a nitrogen atmosphere, introduced hydrogen and copper acetylacetonate at a flow ratio of 1:2.1, deposited for 56 min, calcined at 440 ° C for 10 h, immersed in 20% hydrofluoric acid with a mass fraction of 1.8 times the mass of the silica fiber, washed at 30 kHz for 32 min, and dried at 45 ° C for 11.5 h to obtain foamed copper fiber; (5) Mix barium acetate, calcium acetate, titanium dioxide, zirconium dioxide, deionized water and citric acid in a mass ratio of 1:0.2:0.3:0.05:8:0.4 to obtain a piezoelectric powder precursor; spray the piezoelectric powder precursor 0.35 times the mass of the foam copper fiber onto the foam copper fiber, heat to 270°C, calcine for 6 hours, then heat to 530°C, calcine for 11 hours, continue to heat to 780°C, calcine for 10 hours, and obtain a piezoelectric conductive layer fiber; (6) The piezoelectric conductive layer fiber, anhydrous ethanol, 2'-hydroxy-4'(3-methyl-2-butenyloxy)acetophenone and glacial acetic acid were mixed in a mass ratio of 1:31:0.45:0.1, reacted at 85°C for 9.5 hours under nitrogen protection, washed with anhydrous ethanol and distilled water for 4 times, and freeze-dried at -12°C for 26 hours to obtain a modified matrix; (7) The modified substrate, anhydrous ethanol, 10% sodium hydroxide solution and 2,3-dihydroxy-4-ethoxybenzaldehyde were mixed in a mass ratio of 1:2.5:5.5:0.8, stirred at 20 °C and 150 rpm for 3.5 h, allowed to stand in an ice bath for 38 min, filtered, and washed with anhydrous ethanol five times to obtain chalcone fibers; (8) Chalcone fiber, toluene and triethylamine were mixed in a mass ratio of 1:3.5:0.

03. Under nitrogen protection, a phosphorus trichloride solution in an amount 1.9 times the mass of the chalcone fiber was added at 65°C. The mass ratio of phosphorus trichloride to toluene in the phosphorus trichloride solution was 1:2.

5. After reacting for 36 minutes, the mixture was heated to 115°C. After reacting for 2.3 hours, a decaned acid solution in an amount 4.5 times the mass of the chalcone fiber was added. The mass ratio of decaned acid, toluene and triethylamine in the decaned acid solution was 1:2.2:0.

2. The mixture was reacted for 4.5 hours. The mixture was filtered and dried at 45°C for 7 hours to obtain an antioxidant high-strength glass fiber.